Regional Variation in the Characteristics, Incidence and Outcomes of Out-of-hospital Cardiac Arrest in Australia and New Zealand: Results from the Aus-ROC Epistry - Beck, B; Bray, J; Cameron, P; Smith, K; Walker, T; Grantham, H; Hein, C; Thorrowgood, M; Smith, A; Inoue, M; Smith, T; Dicker, B; et al. (Elsevier, 2018)
Introduction: The aim of this study was to investigate regional variation in the characteristics, incidence and outcomes of out-of-hospital cardiac arrest (OHCA) in Australia and New Zealand. Methods: This was a population-based cohort study of OHCA using data from the Aus-ROC Australian and New Zealand OHCA Epistry over the period of 01 January 2015–31 December 2015. Seven ambulance services contributed data to the Epistry with a capture population of 19.8 million people. All OHCA attended by ambulance, regardless of aetiology or patient age, were included. Results: In 2015, there were 19,722 OHCA cases recorded in the Aus-ROC Epistry with an overall crude incidence of 102.5 cases per 100,000 population (range: 51.0–107.7 per 100,000 population). Of all OHCA cases attended by EMS (excluding EMS-witnessed cases), bystander CPR was performed in 41% of cases (range: 36%–50%). Resuscitation was attempted (by EMS) in 48% of cases (range: 40%–68%). The crude incidence for attempted resuscitation cases was 47.6 per 100,000 population (range: 34.7–54.1 per 100,000 population). Of cases with attempted resuscitation, 28% survived the event (range: 21%–36%) and 12% survived to hospital discharge or 30 days (range: 9%–17%; data provided by five ambulance services). Conclusion: In the first results of the Aus-ROC Australian and New Zealand OHCA Epistry, significant regional variation in the incidence, characteristics and outcomes was observed. Understanding the system-level and public health drivers of this variation will assist in optimisation of the chain of survival provided to OHCA patients with the aim of improving outcomes.
Keywords: Out-of-hospital cardiac arrest; Emergency medical service; Epidemiology; Registry